2008
DOI: 10.1086/591106
|View full text |Cite
|
Sign up to set email alerts
|

Tempt Me Just a Little Bit More: The Effect of Prior Food Temptation Actionability on Goal Activation and Consumption

Abstract: People are often exposed to actionable food temptations (i.e., an immediate opportunity to consume, like when friends offer cookies) and nonactionable food temptations (i.e., no immediate consumption opportunity, like ads for chocolate). The results of three experiments suggest that prior exposure to nonactionable food temptations does not prevent the activation of an eating goal, given a subsequent consumption opportunity, while prior exposure to actionable food temptations prevents such activation. As a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 24 publications
7
95
0
1
Order By: Relevance
“…133 Exposure to food temptations in a supportive environment (that is, where eating the target food is socially proscribed) has also been shown to result in better self-control in a subsequent eating task. 134,135 Experimental studies suggest that this effect is mediated by enhanced salience of the weight control goal, 134 suppressed activation of the eating goal 135 and reduced wanting (but not liking) of the target food. 136 Is it possible to enhance self-regulatory capacity?…”
Section: Theoretical Perspectives On Factors Influencing Self-regulatmentioning
confidence: 99%
“…133 Exposure to food temptations in a supportive environment (that is, where eating the target food is socially proscribed) has also been shown to result in better self-control in a subsequent eating task. 134,135 Experimental studies suggest that this effect is mediated by enhanced salience of the weight control goal, 134 suppressed activation of the eating goal 135 and reduced wanting (but not liking) of the target food. 136 Is it possible to enhance self-regulatory capacity?…”
Section: Theoretical Perspectives On Factors Influencing Self-regulatmentioning
confidence: 99%
“…We propose that when an external agent provides healthy food, people infer that they have made progress on their health goal and subsequently activate the competing motive to satisfy their appetite. Notably, hunger ratings were similar among those who sampled an item framed as tasty compared to those in the no-sample condition, which suggests that tasty food did not intensify the motive to fulfill one's appetite (as in research on reverse-alliesthesia; Wadhwa, Shiv, and Nowlis 2008), nor did it activate the goal to restrict one's appetite (as in research on actionable temptations; Geyskens et al 2008). We did not state any prediction for imposed tasty eating, and because tasty eating had no impact relative to not sampling anything, we can conclude that imposed healthy sampling drives the increase in participants' appetite.…”
Section: Resultsmentioning
confidence: 98%
“…The desire to eat healthy thus competes with the desire to fulfill one's appetite, such that people experience a selfcontrol conflict between eating healthy and eating freely (Geyskens et al 2008;Herman and Polivy 1975;Loewenstein 1996;Muraven and Baumeister 2000;Ramanathan and Williams 2007;Stroebe et al 2008;Vohs and Faber 2007). Not only does healthy eating require certain restrictions, but people's belief that healthy food is generally less fulfilling than unhealthy alternatives further increases the conflict.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Because such weak cues do not appear to warrant increased vigilance in terms of dietary restraint, small temptations often 'fly under the radar', resulting in increased consumption (Coelho do Vale, Pieters, & Zeelenberg, 2008). Relatedly, research has shown that exposure to food cues that include the opportunity to consume a food results in a stronger activation of dietary restraint compared to exposure to weaker, non-actionable food cues (Geyskens, Dewitte, Pandelaere, & Warlop, 2008).…”
Section: Responses To Eating Cuesmentioning
confidence: 99%